Menafsirkan Kunci Kesuksesan Dari Al-Qur’an - Dahlia Dahlia; Indah Berliani; Annisa Choirina; Mega Annisa; Wismanto Wismanto (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
This study aims to examine the meaning of success as found in the Quran and the criteria for success according to the Quran. The research method employed is a qualitative library research approach. The primary data source used is the Quran, with citations of Quranic verses accompanied by translations from the Hadist Web Version 3.0 by Sofyan Efendi. Secondary data is obtained from various exegesis books, such as Tafsir Al-Misbah by M. Quraish Shihab, Jāmi’ al-Bayān ‘an Ta’wīl āy al-Qur’ān by Ibn Jarīr al-Ṭabārī, Jāmi’ al-Bayān li al-Aḥkām al-Qur’ān by Imām al-Qurṭūbi, Tafsir al-Maraghi by Ahmad Muṣaṭfa al-Maragi, Mu’jam Mufradāt li Alfāẓ al-Qur’ān by Al-Ragīb al-Aṣfahānī, Tafsir Al-Qur'anul Madjied An-Nur by T.M. Hasbi Ash-Shiddieqy, as well as hadiths of Prophet Muhammad (peace be upon him). The data analysis technique used is descriptive analysis, where data is systematically analyzed to describe the facts or characteristics of a population or a specific field accurately and conceptually. The research findings reveal that in the Quran, there are three terms that refer to success, namely al-Falah, an-Najah, and al-Fauz. The term "al-Falah" reflects the meaning of success in both worldly and hereafter life, "an-Najah" refers to the meaning of success in worldly life only, while "al-Fauz" pertains to the meaning of success in the hereafter. The criteria for success according to the Quran include belief and piety towards Allah SWT, performing the five daily prayers, supplicating to Allah SWT, actively engaging in work, setting aside a portion of one's income to assist those in need, and seeking Allah SWT's mercy to enter Paradise.